2004
DOI: 10.1074/jbc.m313902200
|View full text |Cite
|
Sign up to set email alerts
|

An Arg307 to Gln Polymorphism within the ATP-binding Site Causes Loss of Function of the Human P2X7 Receptor

Abstract: The P2X 7 receptor is a ligand-gated channel that is highly expressed on mononuclear cells of the immune system and that mediates ATP-induced apoptosis. Wide variations in the function of the P2X 7 receptor have been observed, explained in part by loss-of-function polymorphisms that change Glu 496 to Ala (E496A) and Ile 568 to Asn (I568N). In this study, a third polymorphism, which substitutes an uncharged glutamine for the highly positively charged Arg 307 (R307Q), has been found in heterozygous dosage in 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
153
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(156 citation statements)
references
References 45 publications
2
153
1
Order By: Relevance
“…Net dye uptake indicates the percentage dye uptake induced by BzATP with control (no BzATP treatment) subtracted. The data shown are representative of more than three independent experiments and two-tailed Student's t tests (unpaired) compared to Reference (R) yielded significance levels of <0.05(*), <0.01(**), or <0.001 (***) as shown in b-e of-function (H155Y and A166G) variations are located in the first cysteine-rich domain and only one loss-of-function SNP (R307Q) is at the C-terminus between the second cysteine-rich domain and second membrane-spanning domain (this study and references [57][58][59]). The large extracellular loop is believed to be responsible for ligandbinding and is quite conserved among the P2X receptors, although the fine structure of the ligand-binding pocket is still uncertain.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Net dye uptake indicates the percentage dye uptake induced by BzATP with control (no BzATP treatment) subtracted. The data shown are representative of more than three independent experiments and two-tailed Student's t tests (unpaired) compared to Reference (R) yielded significance levels of <0.05(*), <0.01(**), or <0.001 (***) as shown in b-e of-function (H155Y and A166G) variations are located in the first cysteine-rich domain and only one loss-of-function SNP (R307Q) is at the C-terminus between the second cysteine-rich domain and second membrane-spanning domain (this study and references [57][58][59]). The large extracellular loop is believed to be responsible for ligandbinding and is quite conserved among the P2X receptors, although the fine structure of the ligand-binding pocket is still uncertain.…”
Section: Discussionmentioning
confidence: 74%
“…However, the majority of these have not been validated at the population genetic level and their functional effects are unclear. Five loss-of-function nonsynonymous allelic SNPs in P2X 7 have been described to date, of which three are located in the carboxy-terminal cytoplasmic tail (T357S, E496A, and I568N) and two are in the extracellular loop [54][55][56][57][58]. Cabrini et al have characterized the first gain-of-function polymorphism identified (H155Y) [59].…”
Section: Introductionmentioning
confidence: 99%
“…From the genetics perspective, there are two polymorphisms that lead to a null allele of the P2X7 gene, one of them affecting 1-2% of the Caucasian population, has already been reported (Gu et al, 2004;Skarratt et al, 2005). In addition, one polymorphism was proven to impair ATP-induced IL-1β release from human monocytes and one to affect normal trafficking of this receptor Wiley et al, 2003).…”
Section: P2x7 Receptor: a Possible Mediator Of Orthodontic Mechanotramentioning
confidence: 99%
“…P2X7R has also direct clinical relevance because there are many functional human polymorphisms in the P2X7R gene, which can induce different levels of affinity of these receptors to ATP. One of these polymorphisms, a null allele that occurs in 2% of the Caucasian population, is especially important because it results in reduced expression of the ion channel by 50% (Gu et al, 2004). It is hypothesized that variability in the expression of the P2X7R gene is an important factor in the individual variation to applied orthodontic loads.…”
Section: Orthodontic Mechanotransduction and The Role Of The P2x7 Recmentioning
confidence: 99%
“…4,5 In addition, the K þ ionophore, nigericin, has recently been shown to cause the release of IL-18 from human monocytes. 16 Given the central role of IL-18 in immunity and inflammation, the Glu 496 Ala polymorphism 11 and other, rarer loss-of-function polymorphisms in the P2X 7 receptor 23,24 may have clinical significance. Impaired ATPinduced release of IL-18 may play an important role in diseases where reduced or absent levels of IL-18 are known to increase susceptibility to mycobacteria and certain bacteria, and severity of septic arthritis and endotoxic shock.…”
mentioning
confidence: 99%